1924
DOI: 10.1042/bj0181253
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation of Spermine Phosphate from Semen and Testis

Abstract: IN the course of experimental work on "sperma crystals," extending over the last twenty years, I made an exhaustive study of the literature, as an outcome of which a new chapter must be added to the already remarkable history of an equally remarkable substance. According to the statements of the textbooks, accepted by all writers on the subject, these peculiar crystals were discovered by Bottcher [1865] in human semen and they have since been known as "Bottcher's crystals." Long before Bottcher, however, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

1931
1931
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 1 publication
1
15
0
4
Order By: Relevance
“…The morphology of the crystals was similar to those photographed by Rosenheim (1924). The prostatic secretion is the origin of spermine in human seminal plasma, and the rat prostate also contains high levels of spermine and spermidine (Rosenthal & Tabor, 1956).…”
Section: Discussionsupporting
confidence: 48%
“…The morphology of the crystals was similar to those photographed by Rosenheim (1924). The prostatic secretion is the origin of spermine in human seminal plasma, and the rat prostate also contains high levels of spermine and spermidine (Rosenthal & Tabor, 1956).…”
Section: Discussionsupporting
confidence: 48%
“…Mann (1951b) has shown that cytochrome c is leached out of mammalian spermatozoa on storage and spermine phosphate is believed to be contributed to semen by the prostate (Rosenheim 1924;Harrison 1931Harrison , 1933Bolliger 1935). These substances could therefore be the active compounds of the spermatozoa and accessory fluid, respectively, referred to in the introduction.…”
Section: ( B) Human Spermatozoamentioning
confidence: 99%
“…In all variations tested, including a blank control, AMPA was not oxidized by iodine, and, in turn, did not reduce (decolorize) iodine molecules. Therefore, the AMPA-catalysed destruction of cyclo-O8 was selective, and not a mere reduction of the tetraiodide I4 2-[(I-I-I-I) 2 and/or other color complex was formed, as was proved by the controls RC + KI + glyphosate (4) and RC + KI + glyphosate-Na (5) (Figure 9). The RC + KI + starch + glyphosate (2) solution was colored yellow by the strong acid glyphosate (Figure 9), through H + action onto starch producing the characteristic yellow dextrins [24].…”
Section: Color Assay Formentioning
confidence: 93%